2023
DOI: 10.1038/s41467-023-37373-4
|View full text |Cite
|
Sign up to set email alerts
|

Trade-off between critical metal requirement and transportation decarbonization in automotive electrification

Abstract: Automotive electrification holds the promise of mitigating transportation-related greenhouse gas (GHG) emissions, yet at the expense of growing demand for critical metals. Here, we analyze the trade-off between the decarbonization potential of the road transportation sector and its critical metal requirement from the demand-side perspective in 48 major countries committing to decarbonize their road transportation sectors aided by electric vehicles (EVs). Our results demonstrate that deploying EVs with 40–100% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 90 publications
0
9
0
Order By: Relevance
“…Moreover, the demand for cobalt, together with other critical metals like nickel and manganese, is expected to grow by a factor of 10− 26 by 2050, due to deployment and penetration of automotive electrification. 14 Ni-YSZ shows high electrocatalytic activity for CO 2 conversion, although structural degradation under large applied cathodic potential was reported to occur. 15,16 The reduction process of CO 2 to CO can lead to carbon deposition under a high applied potential, depending on the electrode porosity, especially at the electrode/electrolyte interface.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the demand for cobalt, together with other critical metals like nickel and manganese, is expected to grow by a factor of 10− 26 by 2050, due to deployment and penetration of automotive electrification. 14 Ni-YSZ shows high electrocatalytic activity for CO 2 conversion, although structural degradation under large applied cathodic potential was reported to occur. 15,16 The reduction process of CO 2 to CO can lead to carbon deposition under a high applied potential, depending on the electrode porosity, especially at the electrode/electrolyte interface.…”
Section: ■ Introductionmentioning
confidence: 99%
“…LSCF has the advantage of showing mixed ionic/electronic conductivity over a wide thermal range, although formation of cobalt oxides was observed after prolonged operation. Moreover, the demand for cobalt, together with other critical metals like nickel and manganese, is expected to grow by a factor of 10–26 by 2050, due to deployment and penetration of automotive electrification …”
Section: Introductionmentioning
confidence: 99%
“…3 Lithium-ion batteries are a clean source of renewable energy and ideal for energy storage. 4 Lithium is widely used in electronic equipment and battery-powered vehicles, which has resulted in an abrupt increase in Li demand 5 and consequently a requirement for new Li resources. 6,7 Lithium resources occur mainly in pegmatites, brines, and clays, 8 and are mostly found in Chile, Australia, and Argentina.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Despite the pandemic-induced decline in car sales, EV registration continued to rise and reached over 10 million through 2020, representing 1% of the global passenger car stock (3). However, concerns remain over the embodied emissions of EVs and potential shortages of critical materials, primarily centered around battery manufacturing (4)(5)(6). Previous studies showed that battery manufacturing accounted for between 26 and 46% of the embodied emission of EVs (7)(8)(9)(10), emphasizing the critical role of efficient battery recycling and technological advancements in fostering a sustainable raw material supply for EVs (11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%